Control of meiotic recombination in Arabidopsis: role of the MutL and MutS homologues. (21st July 2006) - Franklin, F.C.H.; Higgins, J.D.; Sanchez-Moran, E.; Armstrong, S.J.; Osman, K.E.; Jackson, N.; Jones, G.H.
Abstract : Immunocytochemistry reveals that the Arabidopsis mismatch repair proteins AtMSH4, AtMLH3 and AtMLH1 are expressed during prophase I of meiosis. Expression of AtMSH4 precedes AtMLH3 and AtMLH1 which co-localize as foci during pachytene. Co-localization between AtMSH4 and AtMLH3 occurs, but appears transient. AtMLH3 foci are not detected in an Atmsh4 mutant. However, localization of AtMSH4 is unaffected in Atmlh3, suggesting that recombination may proceed to dHj (double Holliday junction) formation. Mean chiasma frequency in Atmsh4 is reduced to 1.55 compared with 9.86 in wild-type. In contrast with wild-type, the distribution of residual crossovers in Atmsh4 closely fits a Poisson distribution. This is consistent with a two-pathway model for meiotic crossing-over whereby most crossovers occur via an AtMSH4 -dependent pathway that is subject to interference, with the remaining crossovers arising via an interference-independent pathway. Loss of AtMLH3 results in an approx. 60% reduction in crossovers. Results suggest that dHj resolution can occur, but in contrast with wild-type where most or all dHjs are directed to form crossovers, the outcome is biased in favour of a non-crossover outcome. The results are compatible with a model whereby the MutL complex maintains or imposes a dHj conformation that ensures crossover formation.